THE ENHANCEMENTS’ SKILL OF WRITING POETRY BY PICTURE AND PICTURE DESIGN OF TREE GRADE STUDENTS AT MANGKUYUDAN NO.02 ELEMENTARY SCHOOL SURAKARTA IN THE ACADEMIC YEAR OF 2017/2018 - Bekti Lestari; Retno Winarni; Suharno Suharno (Universitas Sebelas Maret, 2018)
The purpose of this research was to improve the skill of writing poetry by applied picture and picture design for tree grade students in SDN Mangkuyudan No.02 Surakarta on academic year of 2017/2018. It is caused by learning to write poetry that has not done well so class tree grade student have difficulty when asked to write a poem Therefore, the necessary learning strategies and instructional media fun and appropriate. The data collected by interview, observation, test, and documentation techniques. The data validity test were using content validity, triangulation of resource, and triangulation of technique. The result of this research shows the improvement of skill of writing poetry values from pre-action, cycle I until cycle II.